Immunity of EU Institutions in Judicial Proceedings in the EU Member States - Sladič, Jorg (Zbornik znanstvenih razprav (Pravna fakulteta. 1991), 2019)
By virtue of Protocol on the Privileges and Immunities of the European Union and its institutions, the latter are granted immunity of jurisdiction and immunity of enforcement. However, such an immunity is an exception in any procedural law. Both procedural immunities only apply where there is interference with the functioning of the EU, insofar as the EU is not hindered by the ongoing national proceedings in the performing of its tasks and duties, no immunity can be granted. The Court of Justice of the EU applies the doctrine of functional immunity developed for international organisations and the general synallagmatic principle of law of the sincere cooperation between the EU and its Member States (Article 4(3) TEU) to set up duty of institutions to cooperate with national judiciary in national proceedings.
Keywords: autonomous interpretation of term of EU law; avtonomna razlaga pojmov prava EU; EU; Evropska Unija; functional immunity; funkcionalna imuniteta; immunity; imuniteta; international organisation; mednarodna organizacija; nacionalni sodni postopki; načelo lojalnega sodelovanja; national judicial proceedings; principle of sincere cooperation; Protocol No. 7; Protokol št. 7